CHARACTERISTICS OF CHRONIC PAIN USING THE McGILL PAIN QUESTIONNAIRE IN MAINTENANCE HEMODIALYSIS PATIENTS AT MILITARY HOSPITAL 103 - Nguyen Thi Thu Ha,; Hoang Trung Vinh,; Nguyen Van Tu,; Pham Quoc Toan, (Tạp chí Y học Quân sự, 2026)
Objectives: To Assess chronic pain characteristics using the McGill Pain Questionnaire in maintenance hemodialysis patients at Military Hospital 103. Subjects and methods: A cross-sectional study was conducted on 131 maintenance hemodialysis patients at Military Hospital 103 from May 2024 to May 2025. Chronic pain characteristics were assessed using the McGill Pain Questionnaire prior to the hemodialysis session. Results: A total of 83.97% of patients experienced chronic pain. The most common pain locations were the head and facial region (55.0%), extremities (42.7%), and back (39.7%). Most patients reported pain at one or two sites (both accounting for 31.3%). Regarding the sensory dimension of pain, mild pain sensation predominated, with 72.5% of patients having a sensory score ≤ 5. In terms of the affective dimension, the majority of patients reported mild to moderate pain-related emotional responses (96.2%), with affective scores ≤ 6. Based on the total sensory-affective score, pain severity was predominantly mild, as 75.6% of patients had a total score < 10. With respect to pain intensity, most patients experienced mild pain intensity (0-3 points), accounting for 61.1% of cases. Regarding pain perception, chronic pain was mainly distributed within the mild-to-moderate range, with 72.5% of patients reporting a present pain intensity score ≤ 2. There were significant differences in the prevalence of chronic pain according to age, dialysis duration greater than 5 years, and parathyroid hormone (PTH) levels between the pain and non-pain groups (p < 0.05). Conclusions: Pain characteristics assessed using the McGill Pain Questionnaire demonstrated that the sensory, affective, and intensity dimensions of pain were generally mild to moderate in severity; however, the pain was persistent and bothersome to patients. Older age, longer dialysis duration, and elevated parathyroid hormone (PTH) levels were significantly associated with the presence of chronic pain.